Augmented reality-based programming, planning and simulation of a robotic work cell - Pai, Y.S.; Yap, H.J.; Singh, R. (2015)
In this article, the development of an augmented reality-based robotic work cell is presented, consisting of a virtual robot arm, conveyor belt, pallet and computer numerical control machine that simulates an actual manufacturing plant environment. The kinematics of the robot arm is realized using Denavit-Hartenberg's theorem, which enables complete manipulation of the end-effector in three-dimensional space when interacting with other virtual machines. Collision detection is implemented in two areas, namely, modifiable marker-based detection for the robot arm, which detects nearby obstacles as well as integration with object manipulation to pick and place a virtual object around the environment. In addition, an augmented heads-up display overlay displays live information of the current system. The case studies suggest that the proposed system can simulate a collision-free operation while displaying the coordinates of the virtual object, current tool equipped and speed of the conveyor belt, with a percentage error of less than 5.